An in vitro expansion score for tissue‐engineering applications with human bone marrow‐derived mesenchymal stem cells. (10th April 2013) - Bertolo, Alessandro; Mehr, Marco; Janner‐Jametti, Tiziana; Graumann, Ursula; Aebli, Niklaus; Baur, Martin; Ferguson, Stephen J.; Stoyanov, Jivko V.
Abstract: Human bone marrow‐derived mesenchymal stem cells (MSCs) have limited growth potential in vitro and cease to divide due to replicative senescence, which from a tissue‐engineering perspective has practical implications, such as defining the correct starting points for differentiation and transplantation. Time spent in culture before the loss of required differentiation potential is different and reflects patient variability, which is a problem for cell expansion. This study aimed to develop a score set which can be used to quantify the senescent state of MSCs and predict whether cells preserve their ability to differentiate to osteogenic, adipogenic and chondrogenic phenotypes, based on colony‐forming unit (CFU) assay, population doubling time (PDT), senescence‐associated β ‐galactosidase (SA‐ β ‐Gal) activity, cell size, telomere length and gene expression of MSCs cultured in vitro over 11 passages. This set of morphological, physiological and genetic senescence markers was correlated to the ability of MSCs to differentiate. Differentiation efficiency was assessed by marker genes and protein expression. CFUs decreased with increasing passage number, whereas SA‐ β ‐Gal activity and PDT increased; however, the correlation with MSCs' differentiation potential was sometimes unexpected. The expression of genes related to senescence was higher in late‐passage cells than in early‐passage cells. Early‐passage cells underwent efficient osteogenic differentiation, with mid‐passage cells performing best in chondrogenic differentiation. Late‐passage cells preserve only adipogenic differentiation potential. Based on this marker set, we propose a senescence score in which combined markers give a reliable quality control of MSCs, not depending only on mechanistic passage number. Copyright © 2013 John Wiley & Sons, Ltd.